Isolasi Protein dan Bakteri Asam Laktat dari Pangan Tradisional Dali Ni Horbo yang Dimodifikasi sebagai Kandidat Probiotik - Balqis Natasya; Lasminar Meha; Asyrun Lubis; Razoki Razoki; Finna Piska (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Background: Dali ni horbo is a traditional North Sumatran food made from buffalo milk that has potential as a source of protein and lactic acid bacteria (LAB). Its high nutritional content and fermentation process make it a promising candidate for functional food development with probiotic properties. Objective: This study aimed to isolate and characterize proteins and LAB from dali ni horbo produced using different treatments, namely pure buffalo milk, the addition of pineapple juice, and the addition of citrus juice. Methods: Protein isolation was carried out using the ammonium sulfate precipitation method, while LAB were isolated on MRS agar supplemented with CaCO₃. Protein characterization was performed using biuret, ninhydrin, and xanthoprotein tests. LAB characterization included Gram staining, catalase test, and bile salt tolerance test. Results: The results showed that the protein isolate obtained using pineapple as a coagulant had the highest yield (2.3321 g) compared to citrus (1.8516 g). All protein isolates tested positive for biuret, ninhydrin, and xanthoprotein, indicating the presence of peptide bonds, amino acids, and aromatic groups. A total of 18 LAB isolates were obtained, all of which were Gram-positive, rod-shaped, catalase-negative, and tolerant to bile salts. Conclusion: Dali ni horbo has strong potential as a source of protein and probiotic candidates, indicating its applicability as a functional food to support health.